Bionic self-crimping material and application of bionic self-crimping material in nerve field
By designing a biomimetic self-curling material, and utilizing the differences in cross-linking density and dynamic water migration, the nerve ends can be autonomously curled and stably adhered. This solves the problems of size adaptation and suturing complexity of traditional nerve repair materials, and improves nerve regeneration and limb function recovery.
Patent Information
- Application Number
- CN202511143215.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-21
AI Technical Summary
Traditional nerve repair materials are difficult to match with the dynamic deformation of nerve tissue, have size limitations, are prone to unstable adhesion and inflammatory reactions at the moist tissue interface, and the suturing operation is complicated, which affects the nerve regeneration effect.
A biomimetic self-curling material was designed. By photopolymerizing acrylic acid with N-hydroxysuccinimide, chitosan and glutaraldehyde to form a hydrogel, epigallocatechin gallate was introduced. The structure of mimosa leaf was simulated by the difference in crosslinking density and dynamic water migration, so as to achieve autonomous curling and stable adhesion of the material, avoiding the need for suture fixation.
The material can automatically curl into a tube within seconds to match nerve ends of different thicknesses, forming a stable adhesive layer, reducing the risk of inflammation, simplifying the operation, promoting nerve regeneration, reducing the probability of infection, improving the efficiency of nerve electrical signal transmission, and restoring limb function to near normal.
Smart Images

Figure BDA0005550173650000081 
Figure BDA0005550173650000091
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanomaterials technology, specifically to a biomimetic self-curling material and its application in the field of the nervous system. Background Technology
[0002] Peripheral nerve injury (PNI) is a common clinical condition, often caused by trauma, surgical complications, or neurotumors, affecting over one million patients globally each year. Limited functional recovery has become a major public health challenge. Traditional repair methods primarily rely on end-to-end suturing techniques, but this procedure is prone to axonal misalignment, nerve entanglement, and secondary injury, and is highly complex. While emerging pre-formed nerve conduits provide biological support, they struggle to precisely adapt to the diameter differences between individuals and nerve regions, especially at moist tissue interfaces where unstable adhesion, displacement, or even detachment can occur.
[0003] While existing neural scaffolds (such as chitosan, collagen, or synthetic polymer conduits) possess a certain degree of biocompatibility, they still require suture fixation. This not only prolongs surgical time but also easily induces local inflammation due to mechanical rigidity, hindering Schwann cell activity and axonal regeneration. Therefore, ideal neural repair materials urgently need to overcome three major bottlenecks: first, achieving dynamic deformation matching with nerve tissue to avoid the size limitations of pre-formed scaffolds; second, establishing a stable, moist tissue adhesion interface to replace suture operations that easily induce inflammatory reactions; and third, integrating the delivery function of bioactive factors to synergistically promote nerve regeneration.
[0004] Inspired by the stimulus-responsive curling behavior of the mimosa plant, researchers have proposed a design concept for a biomimetic self-curling material. This involves mimicking the rapid deformation of mimosa leaves upon contact with stimuli to develop a bioadhesive tape that can actively adapt to nerve curvature and instantly wrap around the nerve. Upon contact with a moist nerve surface, this material generates asymmetric swelling stress through its internal gradient cross-linked structure, driving the planar membrane structure to spontaneously curl into a tubular shape, seamlessly covering the damaged nerve end. Simultaneously, through the synergistic effect of covalent and hydrogen bonds, it achieves strong adhesion in a moist environment, forming a bio-integrated interface resistant to mechanical traction. This biomimetic strategy not only promises to solve the size adaptation problem of traditional scaffolds, but its seamless operation characteristics can also significantly reduce the risk of surgical damage, providing a new pathway for constructing a dynamically responsive neural regeneration platform. Summary of the Invention
[0005] The purpose of this invention is to provide a biomimetic self-curling material and its application in the field of the nervous system, so as to solve the problems existing in the prior art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a biomimetic self-curling material, wherein the material is prepared by ultraviolet light photopolymerization of acrylic acid and acrylic acid-N-hydroxysuccinimide, adding chitosan and glutaraldehyde to form a hydrogel, and introducing epigallocatechin gallate into the chitosan-acrylic acid network.
[0007] Furthermore, the hydrogel contains NHS groups, which, through covalent cross-linking, allow it to firmly adhere to the nerve stump, forming a dense gap.
[0008] Furthermore, after the hydrogel comes into contact with the surface of nerve tissue, it can absorb water and actively change its shape, instantly transforming from a planar membrane structure into a tubular structure, thereby achieving a tight connection and bridging between the two sides of the severed nerve.
[0009] Furthermore, a method for preparing a biomimetic self-curling material includes the following preparation steps:
[0010] (1) Dissolve acrylic acid in deionized water, add 0.8-1.2% N-hydroxysuccinimide acrylate by mass and dissolve it completely; then add 2% chitosan powder by mass, stir to dissolve, then add 0.3-0.7% plant phenol antioxidant by mass, stir in the dark for 30 min to form a homogeneous solution; finally add 0.15-0.25% photoinitiator by mass and continue stirring to mix; filter the solution through a filter membrane for later use.
[0011] (2) The filtered solution was uniformly coated on the surface of a double-layer membrane substrate with a diameter of 75 mm and irradiated for 30 min under a 365 nm wavelength and 10 W power ultraviolet light source to form a primary hydrogel network.
[0012] (3) Glutaraldehyde aqueous solution was slowly added to the surface of the nascent hydrogel until it was completely saturated, and then transferred to an oven at 35°C and allowed to stand and dry for 6 hours to form a cross-linked gradient structure with a dense upper layer and a sparse lower layer.
[0013] (4) After cutting the dried material, seal it in a plastic bag and store it in an environment of -20℃.
[0014] Furthermore, in step (1), the mass fraction of acrylic acid is 18-22%.
[0015] Furthermore, the plant phenolic antioxidant in step (1) is epigallocatechin gallate.
[0016] Furthermore, the photoinitiator in step (1) is α-ketoglutaric acid.
[0017] Furthermore, in step (1), the pore size of the filter membrane is 0.4 μm.
[0018] Furthermore, the dropping rate in step (3) is 0.06 mL / s.
[0019] Furthermore, in step (3), the mass fraction of glutaraldehyde is 0.4% to 0.7%.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The present invention provides a biomimetic self-curling bioadhesive tape prepared by ultraviolet light photopolymerization of acrylic acid and acrylic acid-N-hydroxysuccinimide, adding chitosan and glutaraldehyde to form a hydrogel, and introducing epigallocatechin gallate into the chitosan-acrylic acid network, which brings a breakthrough progress to nerve repair.
[0022] First, after this material comes into contact with moist nerves, it can autonomously curl into a tubular shape within seconds by simulating the structural design of a mimosa leaf by utilizing the difference in cross-linking density and the dynamic migration of water. The use of a three-channel microfluidic chip enables the directional and orderly diffusion of glutaraldehyde in the nascent hydrogel, improving precision and thus expanding the matching degree for nerve ends of different thicknesses. During the operation, there is no need to prepare scaffolds of various sizes, thus simplifying the operation and getting rid of the limitation of traditional nerve conduits that rely on pre-formed sizes.
[0023] Secondly, the active groups on the surface of the material form a strong chemical connection with the nerve tissue, while the natural component chitosan produces strong physical adsorption, forming a stable adhesive layer in a humid environment, avoiding the risk of sutures chafing and inflammation of fragile nerves, and achieving sutureless fixation;
[0024] Finally, the material utilizes chitosan's inherent antibacterial properties, reducing the probability of postoperative infection. Epigallocatechin gallate is introduced to scavenge free radicals at the site of nerve damage. Its degradation cycle is synchronized with the natural healing of the nerve, eliminating the need for a second surgery. Using this material results in smoother nerve signal transmission, reduced atrophy of the target muscle, and near-normal recovery of limb motor function. Detailed Implementation
[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] To more clearly illustrate the method provided by the present invention, the following embodiments are provided in detail. The testing methods for various indicators of a biomimetic self-curling material prepared in the following embodiments are as follows:
[0027] Tensile test: Tensile tests were performed using a universal tensile testing machine (MARK-10, New York, USA) to evaluate the tensile strength and elongation of the samples; SCT was cut into rectangular slices 10 mm wide and 1 mm thick at a cutting speed of 13 mm / s; each sample was tested at least three times until the hydrogel broke.
[0028] Rheological experiments: The rheological properties of SCT were tested at 25°C using an Anton Paar MCR302 rheometer (Anton Paar Ltd., UK). The gel was placed on a circular test plate with a diameter of 6 mm and a spacing of 1 mm, and the storage modulus (G′) and loss modulus (GI) were measured. The scanning test was performed at a constant frequency of 1 Hz, and the strain value ranged from 0.01% to 100%. Each sample was tested three times.
[0029] Adhesion properties: The adhesion of the hydrogel was measured using a universal tensile testing machine (MARK-10) attached to pigskin. First, the frozen pigskin was thawed in a 37°C water bath. Then, the pigskin and small tract tissue (SCT) were cut into rectangular slices with dimensions of 20mm × 10mm × 1mm. The adhesion strength between the attached tissue and the sample was measured using the 180° peel test method, with the peel speed set at 13mm / s. Each sample was tested three times.
[0030] Hemolytic activity assay: The blood compatibility of SCT was studied by measuring the absorbance of hemoglobin released after erythrocyte lysis. Blood from adult rabbits was collected in centrifuge tubes containing 10 mL EDTA, gently shaken, and centrifuged at 1500 rpm for 5 min. Serum was then removed, and an equal volume of freshly prepared PBS solution was added. This step was repeated three times to thoroughly remove residual fragmented red blood cells (RBCs). Finally, the red blood cells were diluted with PBS to a concentration of 1 × 10⁻⁶. 8 1 mL of red blood cell suspension was collected; then SCT1, SCT2, and SCT4 hydrogels were added to the red blood cell suspension, with PBS as a negative control and Triton X-100 (1%) as a positive control; after incubation at 37°C for 60 min, the supernatant was collected and centrifuged at 1500 rpm for 5 min; the supernatant was added to a 96-well plate, and the absorbance of the solution was measured using a microplate reader (Imark, USA); the hemolysis rate was calculated using the following formula:
[0031] Hemolysis rate (%) = (As-Ac) / At × 100%, where AS, Ac and At represent the absorbance of the sample, PBS and Triton-X100 group at 540 nm, respectively.
[0032] Cell compatibility (live / dead cell assay): The effect of SCT extract on RSC96 cell proliferation was investigated using a live / dead cell assay to assess the cytotoxicity of the material; RSC96 cells were seeded in 35 mm Corning dishes (cell density 9 × 10⁶ cells per well). 5 SCT4 cells were cultured in DMEM / high glucose medium (Hyclone, USA) containing 10% fetal bovine serum (Gibco, USA) at 37°C in a CO2 incubator. Filtered culture medium containing SCT4 cells was added to the experimental group culture dishes. At specific incubation time points (24, 48, and 72 h), cells were stained using a calcein-AM / PI kit (Solarbio, China) to distinguish between live and dead cells (live cells: green; dead cells: red). Fluorescence images of cells at 490 and 545 nm wavelengths were acquired using a Zeiss inverted fluorescence microscope (Germany). Cells were then digested with trypsin-EDTA (Gibco, USA) and transferred to 96-well plates, and the absorbance of RSC96 cells was measured. The absorbance of the suspension was measured at 540 nm using an enzyme marker (Imark, USA). Each sample was tested three times.
[0033] Cell compatibility (CCK-8) assay: The effect of SCT extract on the viability of RSC96 cell line was quantitatively analyzed using a cell counting kit (Toyo Pharmaceutical Co., Ltd., Japan). RSC96 cell suspension (100 μL per well) was seeded in 96-well plates. DMEM medium was used as the control group, and different concentrations of SCT4 extract (5, 2.5, 1, 2.0, and 0.6 mg / mL) were added to the experimental groups. -1 The concentration of ) was determined; the culture plate was pre-incubated in a 37°C, CO2 incubator; 10 μL of LCK-8 working solution was added to each well, and incubation was continued for 2 hours. The absorbance was then measured at 540 nm using a microplate reader (Imark, USA); each sample was tested at least three times; cell viability was calculated using the following formula:
[0034] Cell viability (%) = (Asapmple - Ablank) / (Acontrol - Ablank) × 100%.
[0035] Antibacterial test: The antibacterial rate of different hydrogels was determined by colony counting and inhibition zone methods. Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli were used as bacterial models in the experiment. Each sample group was tested three times in total, and cell viability was calculated.
[0036] Example 1
[0037] (1) Dissolve acrylic acid in deionized water at a mass fraction of 18%, add 0.8% N-hydroxysuccinimide acrylate at a mass fraction of 60 rpm and stir thoroughly for 30 min to dissolve; then add 2% I-81-9132 chitosan powder at a mass fraction of 60 rpm and continue stirring to dissolve. Then add 0.3% epigallocatechin gallate at a mass fraction of 60 rpm and stir in the dark for 30 min to form a homogeneous solution; finally add 0.15% α-ketoglutarate photoinitiator at a mass fraction of 60 rpm and continue stirring and mixing for 20 min; filter the solution through a 0.4 μm pore size filter membrane for later use.
[0038] (2) The filtered solution was uniformly coated on the surface of a double-layer membrane substrate with a diameter of 75 mm and a coating amount of 4.4 g. It was then irradiated for 30 min under a 365 nm wavelength and 10 W power ultraviolet light source to form a primary hydrogel network.
[0039] (3) Fix the three-channel microfluidic chip to the bracket and adjust the outlet height to 0.5 mm from the surface of the nascent hydrogel; connect inlet A to the glutaraldehyde solution storage tank, which contains 0.4% glutaraldehyde aqueous solution; connect inlet B / C to the nitrogen cylinder; place the UV-cured nascent hydrogel on the temperature control platform and control the temperature at 25℃; turn on the nitrogen flow at inlet B / C, with a pressure of 0.02 MPa and a flow rate of 0.5 mL / min for 5 s; start the glutaraldehyde solution flow at inlet A, with a flow rate of 0.03 mL / min for 120 s; simultaneously, use a nitrogen buffer flow with a flow rate of 0.2 mL / min to clamp the solution flow and ensure laminar contact; then turn off all fluids and keep the environment at 25℃ and 60% RH for 10 min; transfer to a 35℃ oven and let it stand for 6 h to form a cross-linked gradient structure with a dense upper layer and a sparse lower layer.
[0040] (4) After cutting the dried material, seal it in a plastic bag and store it in an environment of -20℃.
[0041] Example 2
[0042] (1) Dissolve acrylic acid in deionized water at a mass fraction of 20%, add N-hydroxysuccinimide acrylate at a mass fraction of 1.0%, and stir thoroughly for 30 min at a stirring speed of 60 rpm; then add chitosan powder at a mass fraction of 2%, continue stirring to dissolve, then add epigallocatechin gallate at a mass fraction of 0.5%, and stir at 60 rpm in the dark for 30 min to form a homogeneous solution; finally add α-ketoglutarate photoinitiator at a mass fraction of 0.2%, and continue stirring and mixing for 20 min; filter the solution through a 0.4 μm pore size filter membrane for later use.
[0043] (2) The filtered solution was uniformly coated on the surface of a double-layer membrane substrate with a diameter of 75 mm and a coating amount of 4.6 g. It was then irradiated for 30 min under a UV light source with a wavelength of 365 nm and a power of 10 W to form a primary hydrogel network.
[0044] (3) Fix the three-channel microfluidic chip to the bracket and adjust the outlet height to 0.5 mm from the surface of the nascent hydrogel; connect inlet A to the glutaraldehyde solution storage tank, which contains a 0.55% glutaraldehyde aqueous solution; connect inlet B / C to the nitrogen cylinder; place the UV-cured nascent hydrogel on the temperature control platform and control the temperature at 25℃; turn on the nitrogen flow at inlet B / C, with a pressure of 0.02 MPa and a flow rate of 0.5 mL / min for 5 s; start the glutaraldehyde solution flow at inlet A, with a flow rate of 0.03 mL / min for 120 s; simultaneously, use a nitrogen buffer flow with a flow rate of 0.2 mL / min to clamp the solution flow and ensure laminar contact; then turn off all fluids and keep the environment at 25℃ and 60% RH for 10 min; transfer to a 35℃ oven and let it stand for 6 h to form a cross-linked gradient structure with a dense upper layer and a sparse lower layer.
[0045] (4) After cutting the dried material, seal it in a plastic bag and store it in an environment of -20℃.
[0046] Example 3
[0047] (1) Dissolve acrylic acid in deionized water at a mass fraction of 22%, add N-hydroxysuccinimide acrylate at a mass fraction of 1.2%, and stir thoroughly for 30 min at a stirring speed of 60 rpm. Then add chitosan powder at a mass fraction of 2%, continue stirring to dissolve, and then add epigallocatechin gallate at a mass fraction of 0.7%, and stir at 60 rpm in the dark for 30 min to form a homogeneous solution. Finally, add α-ketoglutarate photoinitiator at a mass fraction of 0.25%, and continue stirring and mixing for 20 min. Filter the solution through a 0.4 μm pore size filter membrane for later use.
[0048] (2) The filtered solution was uniformly coated on the surface of a double-layer membrane substrate with a diameter of 75 mm and a coating amount of 4.8 g. It was then irradiated for 30 min under a 365 nm wavelength and 10 W power ultraviolet light source to form a primary hydrogel network.
[0049] (3) Fix the three-channel microfluidic chip to the bracket and adjust the outlet height to 0.5 mm from the surface of the nascent hydrogel; connect inlet A to the glutaraldehyde solution storage tank, which contains 0.7% glutaraldehyde aqueous solution; connect inlet B / C to the nitrogen cylinder; place the UV-cured nascent hydrogel on the temperature control platform and control the temperature at 25℃; turn on the nitrogen flow at inlet B / C, with a pressure of 0.02 MPa and a flow rate of 0.5 mL / min for 5 s; start the glutaraldehyde solution flow at inlet A, with a flow rate of 0.03 mL / min for 120 s; simultaneously, use a nitrogen buffer flow with a flow rate of 0.2 mL / min to clamp the solution flow and ensure laminar contact; then turn off all fluids and keep the environment at 25℃ and 60% RH for 10 min; transfer to a 35℃ oven and let it stand for 6 h to form a cross-linked gradient structure with a dense upper layer and a sparse lower layer.
[0050] (4) After cutting the dried material, seal it in a plastic bag and store it in an environment of -20℃.
[0051] Comparative Example 1
[0052] The difference between Comparative Example 1 and Example 2 lies in step (1). Step (1) is changed as follows: acrylic acid is dissolved in deionized water at a mass fraction of 20%, and 1.0% of acrylate-N-hydroxysuccinimide ester is added and stirred thoroughly for 30 minutes at a stirring speed of 60 rpm. Then, 2% of chitosan powder is added and stirred at 60 rpm in the dark for 30 minutes to form a homogeneous solution. Finally, 0.2% of α-ketoglutarate photoinitiator is added and stirred continuously for 20 minutes. The solution is then filtered through a 0.4 μm pore size filter membrane for later use. The remaining steps are the same as in Example 2.
[0053] Comparative Example 2
[0054] The difference between Comparative Example 2 and Example 2 lies in step (1). Step (1) is changed as follows: acrylic acid is dissolved in deionized water at a mass fraction of 20%, and N-hydroxysuccinimide acrylate at a mass fraction of 1.0% is added and stirred thoroughly for 30 minutes at a stirring speed of 60 rpm. Then, CHS collagen at a mass fraction of 2% is added and stirred until dissolved. Epigallocatechin gallate at a mass fraction of 0.5% is added and stirred at 60 rpm in the dark for 30 minutes to form a homogeneous solution. Finally, α-ketoglutarate photoinitiator at a mass fraction of 0.2% is added and stirred continuously for 20 minutes. The solution is then filtered through a 0.4 μm pore size filter membrane for later use. The remaining steps are the same as in Example 2.
[0055] Comparative Example 3
[0056] The difference between Comparative Example 3 and Example 2 lies in step (2). Step (2) is changed to: uniformly coating the filtered solution onto the surface of a double-layer membrane substrate with a diameter of 75 mm, with a coating amount of 4.6 g, and drying at 50 °C for 3 h to form a nascent hydrogel network; the remaining steps are the same as in Example 2.
[0057] Comparative Example 4
[0058] The difference between Comparative Example 4 and Example 2 lies in step (3). Step (3) is changed to: slowly adding 0.55% glutaraldehyde aqueous solution to the surface of the nascent hydrogel until it is completely saturated, with a dropping rate of 0.06 mL / s, and then transferring it to a 35°C oven to dry for 6 hours to form a cross-linked gradient structure with a dense upper layer and a sparse lower layer; the remaining steps are the same as in Example 2.
[0059] Example of effect
[0060] Table 1 below presents the performance analysis results of a biomimetic self-curling material using Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention.
[0061] Table 1
[0062]
[0063]
[0064] A comparison of experimental data on tensile strength, elongation at break, and storage modulus between the examples and comparative examples reveals that the biomimetic self-curling bioadhesive tape provided by this invention, through ultraviolet light photopolymerization of acrylic acid and acrylic acid-N-hydroxysuccinimide, upon contact with moist nerves, utilizes the difference in cross-linking density and dynamic water migration to simulate the structural design of a mimosa leaf, autonomously curling into a tubular shape within seconds. This allows it to match nerve ends of varying thicknesses, eliminating the need for preparing multiple sizes of scaffolds during surgery, thus simplifying the procedure and overcoming the limitations of traditional nerve conduits that rely on pre-formed sizes. A comparison of experimental data on wet adhesion between the examples and comparative examples shows that the surface-active groups of the material prepared by this invention form a strong chemical connection with nerve tissue, while the natural component chitosan generates strong physical adsorption, forming a stable adhesive layer in a moist environment. This avoids the risk of suture injury and inflammation to fragile nerves, achieving sutureless fixation. A comparison of experimental data on antibacterial rate, hemolysis rate, and cell survival rate between the examples and comparative examples reveals that the material prepared in this invention possesses inherent antibacterial capabilities due to chitosan, reducing the probability of postoperative infection. The introduction of epigallocatechin gallate esters scavenges free radicals at the nerve injury site. Its degradation cycle is synchronized with the natural healing of the nerve, eliminating the need for secondary surgery. Using this material results in smoother nerve signal transmission, reduced atrophy of the target muscle, and near-normal recovery of limb motor function. A comparison of experimental data on the stretching and curling time between the examples and comparative examples shows that the three-channel microfluidic chip in this invention enables the directional and orderly diffusion of glutaraldehyde in the nascent hydrogel, improving precision and thus expanding the matching accuracy for nerve ends of varying thicknesses.
[0065] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A biomimetic self-curling material, characterized in that, The material was prepared by ultraviolet photopolymerization of acrylic acid and acrylate-N-hydroxysuccinimide, adding chitosan and glutaraldehyde to form a hydrogel, and introducing epigallocatechin gallate into the chitosan-acrylic acid network.
2. The biomimetic self-curling material according to claim 1, characterized in that, The hydrogel contains NHS groups, which are covalently cross-linked to firmly adhere to the nerve stump, forming a dense gap.
3. The biomimetic self-curling material according to claim 1, characterized in that, After the hydrogel comes into contact with the surface of nerve tissue, it can absorb water and actively change its shape, instantly transforming from a planar membrane structure into a tubular structure, thereby achieving a tight connection and bridging between the two sides of the severed nerve.
4. A method for preparing a biomimetic self-curling material, characterized in that, The preparation steps include the following: (1) Dissolve acrylic acid in deionized water, add 0.8-1.2% N-hydroxysuccinimide acrylate (by mass) and dissolve completely; then add 2% chitosan powder (by mass) and stir to dissolve. After stirring, add 0.3-0.7% phytophenol antioxidant (by mass) and stir in the dark for 30 minutes to form a homogeneous solution; finally, add 0.15-0.25% photoinitiator (by mass) and continue stirring to mix; filter the solution through a filter membrane for later use. (2) The filtered solution was uniformly coated on the surface of a double-layer membrane substrate with a diameter of 75 mm and irradiated for 30 min under a 365 nm wavelength and 10 W power ultraviolet light source to form a primary hydrogel network. (3) Fix the three-channel microfluidic chip to the bracket; connect inlet A to the glutaraldehyde solution storage tank, which contains glutaraldehyde aqueous solution, and connect inlet B / C to the nitrogen cylinder; place the UV-cured nascent hydrogel on the temperature control platform and control the temperature at 25℃; turn on the nitrogen flow at inlet B / C, with a pressure of 0.02MPa and a flow rate of 0.5mL / min for 5s; Start the inlet A glutaraldehyde solution flow at a flow rate of 0.03 mL / min for 120 s; simultaneously, use a nitrogen buffer flow at a flow rate of 0.2 mL / min to clamp the solution flow and ensure laminar contact; then shut off all fluids and maintain a static environment of 25°C and 60% RH for 10 min; transfer to a 35°C oven and dry for 6 h to form a cross-linked gradient structure with a dense upper layer and a sparse lower layer. (4) After cutting the dried material, seal it in a plastic bag and store it in an environment of -20℃.
5. The method for preparing a biomimetic self-curling material according to claim 4, characterized in that, In step (1), the mass fraction of acrylic acid is 18-22%.
6. The method for preparing a biomimetic self-curling material according to claim 4, characterized in that, The plant phenolic antioxidant in step (1) is epigallocatechin gallate.
7. The method for preparing a biomimetic self-curling material according to claim 4, characterized in that, In step (1), the photoinitiator is α-ketoglutaric acid.
8. The method for preparing a biomimetic self-curling material according to claim 4, characterized in that, The filter membrane pore size in step (1) is 0.4 μm.
9. The method for preparing a biomimetic self-curling material according to claim 4, characterized in that, In step (3), the outlet height is adjusted to 0.5 mm from the surface of the nascent hydrogel.
10. The method for preparing a biomimetic self-curling material according to claim 4, characterized in that, In step (3), the mass fraction of glutaraldehyde is 0.4% to 0.7%.
Citation Information
Cited By
Gradient cross-linking self-curling neural restoration hydrogel film as well as preparation method and application of gradient cross-linking self-curling neural restoration hydrogel film
CN120324682A